Linguistic Traces of Subjectivity and Dissent. A Discursive Analysis of Inclusive Language in Argentina - Tosi, Carolina Luciana (2021)
In Argentina, the so-called “inclusive language” aims at avoiding the bias for a particular sex or gender and objects to a grammatical binary system (feminine – masculine). Although in most Spanish-speaking countries, inclusive language has been limited to the realms of activism, gender studies and a certain type of public administration, in Argentina, its use has been extended to different social spheres, mostly urban. Considering such context, this work aims to investigate the inclusive language in Spanish and characterize its most relevant resources in a series of public texts that circulated in Argentina between 2018 and 2020. On the one hand, its origin is explained, differentiating it from non-sexist language and the different theoretical positions around inclusive language are exposed. On the other hand, from the Dialogical Approach to Argumentation and Polyphony, this paper proposes to address inclusive language resources as subjectivity and polyphony marks which evidence certain aspects of the discourse of patriarchy, with respect to which there is dissent; therefore, inclusive language resources show viewpoints that were once silenced and rejected. For this, a corpus of various speeches is addressed, made up of outdoor urban inscriptions, flyers (advertisements), audiovisual informative speeches and digital press, written in inclusive language, between 2018 and 2020. Throughout the paper it is warns that the inclusive language marks, such as –e and x, are traces of the “heterogeneity shown marked” that object to grammatical binarism and convey comments by the subject about their own enunciation, alluding to the image of previous sexist and patriarchal discourses with whom they disagree. The analysis reveals that the words or expressions in which inclusive language resources are employed (-e and x) work as traces of harassed identities and manifest comments by the speaker on their own enunciation. This way, this research shows that gender inclusive language holds conflict linguistic marks which point to historically denied dissidence forms, linked to gender identity and the assertion of collective rights. Finally, this article aims at, on the one hand, contributing to the description of Argentinean Spanish, and on the other, promoting reflection in favor of linguistic education. Undoubtedly, opening instances of debate on the subject can have an impact on the deepening of linguistic reflection and the training of speakers who contribute to forging a more egalitarian society, one which is inclusive and respectful of differences.